Priming effect varies with root order: A case of Cunninghamia lanceolata. (September 2021) - Yin, Liming; Zhang, Tingshuang; Dijkstra, Feike A.; Huo, Changfu; Wang, Peng; Cheng, Weixin
Abstract: Plant litter inputs can influence soil organic carbon (SOC) decomposition via the priming effect. However, our understanding of the priming effect and underlying mechanisms is primarily from studies with leaf litter addition, while little is known about root litter effects, particularly of woody plants. Here, using a 13 C natural tracer approach, we conducted a 12-week incubation experiment to investigate litter decomposition and priming effect of mature-tree root orders (1st to 5th) of Cunninghamia lanceolata (Lamb.) Hook. We explored how litter decomposition and the priming effect were related to microbial biomass of main groups, enzyme activities, and root tissue chemistry. Root litter decomposition rates increased with increasing root order, especially during the first 4 weeks, which was likely due to higher non-structural C and lower tannin concentrations for higher order roots. A negative priming effect occurred at this initial intensive stage when microbes may have preferred utilizing litter-derived labile C. Subsequently, the priming effect switched to positive, and showed larger priming effects for the higher order roots than the lower order ones. Higher order roots also showed higher fungi to bacteria ratios and enzyme activities than the lower order roots. These patterns of fungi to bacteria ratios and enzyme activities and thus the priming effect could be attributed to the difference in carbon:nitrogen ratio among root orders. Overall, we for the first time provide strong evidence for the effect of root order on the priming effect, and thus highlight that separating root litter based on root order is necessary for accurately evaluating its influence on SOC decomposition. Graphical abstract: Image 1 Highlights: Woody root decomposition and priming effect among root orders are investigated. Root decomposition increases with root order especially at the first 4 weeks. Root decomposition relates to non-structural carbon and lower tannin concentrations. Microbial enzyme activities increase with root order due to carbon:nitrogen ratio. Higher order roots induce a higher priming effect than lower order roots.